Nuosavybės santykių modelis sovietiniame Lietuvos kaime. Stungių kaimo atvejis - Kačiuška, Žilvinas (Lietuvos istorijos studijos, 2004)
After a collapse of the Soviet Union, Lithuania (as well as most of Central and East European countries) is sometimes entitled as "the second echelon", agrarian region or the periphery of Western civilisation. The cultural and economical lag of Lithuania is often said to be caused by a mental gap, which was constructed by a model of collectivism and planned economy. Herewith, slowly changing categories in cognition impact reflections on market economy model and its mode of functioning. The ideological and physical installation of collectivism and disruption of private sector during Sovietism contradicted the centenary traditions of private farming in Lithuania. With the recovery of independence, speedy land economy, property and social reforms in the village met the expressions of collectivism practice and shadow private farming tradition that were implanted during Sovietism. This evoked the feeling of uncertainty and social strain in the village, and often results in a form of mass protest of farmers. The purpose of this study is to determine the status of property relations in the rural community during Sovietism by using a private sector concept. The research comprises of three chapters: 1. Soviet economic and social policy in Lithuanian village. 2. Property relations in Lithuanian Soviet village. 3. The relationship between differentiation of rural society and property sectors in Sovietism. During Sovietism private sector was being eliminated from the market contrary to state sector, because it was treated as a rudiment of commercial activities and therefore contradicted the society model that was constructed by the official Communist ideology. Legally, a person was enabled to possess private property only for uncommercial purposes. All personal and real estates as well as their output were controlled by the state. The Soviet power structures were unsuccessful in totally eliminating private sector and practically, private sector, producing surplus production for commercial purposes, remained a half-legal, informal and shadow structure in village. For the rural society it was one of the main sources of incomes, resources for which were rendered from the state sector. The survival of individual (private) farming tradition in Sovietism that was expressed by possessing individual farmland and realising surplus product determined the vitality of private sector. Proprietors used to spend almost all of their time free from work in the collective or state farms for own land cultivation and surplus product production. The shadow status of the private sector influenced a perverted evolution of property relations formation, which distinguished by a private sector development process that dubbed state sector functions. This resulted in increasing volume of private farms and the process of transformation of collective or state farms into cooperative associations during and after the collapse of the Soviet Union. Sovietism in village has formed the specific understanding about economy, its administrative principles and rational behaviour skills, and also a relatively strict social differentiation. Economy management was understood as an execution of the directives from the superior power structures, allocation of tasks and control of their processing. Good execution of a task corresponded to bigger volume of material resources used and smaller amount of tasks received. This was achieved only when having good relations with power structures. According to different accession to resource allocation process, the privileged society groups had formed. In the case of village, the privileged group consisted of representatives from collective or soviet farm ruling layer. Though aforementioned layer had to follow the Soviet power directives and to control the situation in farms, it was also active in private farming activities. The status and its indicative privileges guaranteed the immunity of this ruling layer.